2011
DOI: 10.4306/pi.2011.8.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Serum Homocysteine and Folate Levels in Korean Schizophrenic Patients

Abstract: ObjectiveThis study was conducted to confirm the results of the authors' previous research on schizophrenia manifesting high serum homocysteine and low folate levels. This study is anchored on a theory that a high serum homocysteine concentration affects schizophrenia by virtue of a neurotoxic mechanism, and on a report that some schizophrenia patients with high homocysteine levels benefited from high folate ingestion.MethodsThe serum homocysteine, folate, and vitamin B12 levels of 236 normal-control-group sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
3
19
0
3
Order By: Relevance
“…Some authors [40] have reported no changes, but others [41], [42] have reported increased levels, in untreated patients with schizophrenia. It has also been reported that patients with the 677TT genotype showed higher homocysteine levels than other patients and it was suggested that supplemental folate may be beneficial to some patients with schizophrenia and homocysteinemia due to the genetic defect of methylenetetrahydrofolate reductase [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [40] have reported no changes, but others [41], [42] have reported increased levels, in untreated patients with schizophrenia. It has also been reported that patients with the 677TT genotype showed higher homocysteine levels than other patients and it was suggested that supplemental folate may be beneficial to some patients with schizophrenia and homocysteinemia due to the genetic defect of methylenetetrahydrofolate reductase [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Regland et al 41 were the first to associate increased blood Hcy concentrations with schizophrenia in 1995. The association was latter subject of a meta-analysis in 2006 by Muntjewerff et al 42 who collected data from 8 case-control studies and demonstrated a 70% increase in the risk of schizophrenia for every 5 mM increase in Hcy concentration and many other studies since then have corroborated this hypothesis, [43][44][45][46][47][48][49][50][51][52] although negative results are also present in the literature. 53 Genetic factors associated with Hcy metabolism are also associated with schizophrenia risk.…”
Section: Schizophreniamentioning
confidence: 97%
“…Low folate concentrations are associated with increased Hcy levels and schizophrenia. 48,50 Low betaine plasma concentrations have also been demonstrated in patients with first-episode schizophrenia and can influence Hcy metabolism in these individuals. 59 The link between Hcy metabolism and schizophrenia can be related to fetal hypoxia, altered DNA methylation, and partial antagonistic effect on N-Methyl-D-aspartate (NMDA) glutamatergic neurons.…”
Section: Schizophreniamentioning
confidence: 99%
“…饥荒是一种低蛋白低能量的饮食, 包含各种必需 营养元素的全面匮乏, 那么到底是哪些营养元素与精 神分裂症有直接或间接的联系? 研究发现, 叶酸不足 与神经管的缺陷有关, 而神经管的缺陷与精神分裂症 密切相关 [10] , 进一步分析发现精神分裂症患者的血清 徐飞等: 出生前营养不良致子代易感精神分裂症研究进展 叶酸水平要显著低于正常人群 [11,12] . 另外, 不饱和脂 肪酸 [13] 、维生素A [14] 、维生素D [15] 、铁离子 [16] 、蛋 白质能量营养缺乏 [17] 都被分别报道与精神分裂症相 关联.…”
Section: 流行病学研究unclassified